2016
DOI: 10.7567/jjap.55.1202bc
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxial growth of ε-Ga2O3 thin films on cubic (111) MgO and (111) yttria-stablized zirconia substrates by mist chemical vapor deposition

Abstract: In this study, epitaxial ε-Ga2O3 thin films are successfully grown on cubic (111) MgO and (111) yttria-stablized zirconia (YSZ) substrates by mist chemical vapor deposition. Pure-phase hexagonal ε-Ga2O3 thin films are grown on the two substrates with a c-axis orientation determined by X-ray diffraction (XRD) 2θ–ω scanning. XRD pole figure measurements reveal that the in-plane orientation relationship between the (0001) of ε-Ga2O3 and the (111) of the two substrates is ε-Ga2O3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 31 publications
(37 reference statements)
1
59
0
Order By: Relevance
“…The growth of e-Ga 2 O 3 has been demonstrated on various substrates such as gadolinium gallium garnet (GGG) (cubic), MgO(111), yttria-stabilized ZrO 2 (YSZ)(111), a-(Al x Ga 1Àx ) 2 O 3 (0001), NiO(111), AlN, and GaN. 26,28,85,86 The synthesis conditions that allow for a particular Ga 2 O 3 polymorph strongly depend on the crystallographic mismatch between the substrate and epilayer as well as the surface crystal structure. Some authors have reported that substrates of a cubic material (MgO and YSZ) oriented along the (111) direction allow one to obtain single phase (001)-oriented e-Ga 2 O 3 layers by mist-CVD in a wide range of deposition temperatures (400-700 1C) where typically a-Ga 2 O 3 is obtained on c-plane sapphire.…”
Section: Substrate and Lattice Matchmentioning
confidence: 99%
“…The growth of e-Ga 2 O 3 has been demonstrated on various substrates such as gadolinium gallium garnet (GGG) (cubic), MgO(111), yttria-stabilized ZrO 2 (YSZ)(111), a-(Al x Ga 1Àx ) 2 O 3 (0001), NiO(111), AlN, and GaN. 26,28,85,86 The synthesis conditions that allow for a particular Ga 2 O 3 polymorph strongly depend on the crystallographic mismatch between the substrate and epilayer as well as the surface crystal structure. Some authors have reported that substrates of a cubic material (MgO and YSZ) oriented along the (111) direction allow one to obtain single phase (001)-oriented e-Ga 2 O 3 layers by mist-CVD in a wide range of deposition temperatures (400-700 1C) where typically a-Ga 2 O 3 is obtained on c-plane sapphire.…”
Section: Substrate and Lattice Matchmentioning
confidence: 99%
“…Recent theoretical calculations substantiate these expectations. [ 13 ] Further, the larger bandgap of κ-Ga2normalO3 of about 4.9 eV [ 14–19 ] compared with GaN [ 1 ] (Enormalg3.4 eV) can push the transparency of the devices toward solar‐blind regions enabling infrared detection for extraterrestrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…κ-Ga2normalO3 can be grown heteroepitaxially by several deposition methods, such as pulsed‐laser deposition [ 14,19–26 ] (PLD), halide vapor phase epitaxy [ 18,27–29 ] (HVPE), metal‐organic chemical vapor deposition [ 17,30–35 ] (MOCVD), metal‐organic vapor phase epitaxy [ 36–39 ] (MOVPE), atomic layer deposition, [ 31 ] molecular beam epitaxy [ 40 ] (MBE), plasma‐assisted molecular beam epitaxy [ 41 ] (PAMBE), and mist CVD. [ 15,16,42–49 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, these metastable phases have recently drawn attention due to their interesting properties. [8][9][10][11][12][13][14][15][16][17][18][19] For example, α-Ga 2 O 3 with the corundum structure has a bandgap energy of 5.3 eV. The structure is the same as that of sapphire; therefore, α-Ga 2 O 3 thin films can be grown on inexpensive sapphire substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there are only a limited number of repots on the other structures because they are metastable phases. However, these metastable phases have recently drawn attention due to their interesting properties . For example, α‐Ga 2 O 3 with the corundum structure has a bandgap energy of 5.3 eV.…”
Section: Introductionmentioning
confidence: 99%